2002
DOI: 10.1021/bp0200043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of High Molecular Weight Pullulan Production by Aureobasidium pullulans in Batch Fermentations

Abstract: Of five strains of Aureobasidium pullulans studied, NRRL Y-2311-1 yielded the highest titer (26.2 g/L) of pullulan and formed the lowest amount of melanin-like pigment. Sucrose was superior to glucose as the carbon and energy source on the basis of yield and titer of pullulan produced. Pullulan titer was higher (26.2 vs 5.1 g/L), biomass concentration was lower (6.9 vs 12.7 g/L), and DO was lower (0 vs 60% of saturation) when the fermenter was agitated by a marine propeller compared to Rushton impellers. Pullu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…To culture pullulan, fermentors are often run for long periods of time to maximize pullulan production, on the order of several days. 9 For the hour 3 cells in our study, we have very little exopolymer, and due to the size (39.5 nm) and chemical information, it is apparently entirely uronic acid based. The size of this polymer is sufficient to cause steric repulsion between the fungal macromolecules and the AFM tip, but this repulsion does not prevent the cells from adhering strongly to silicon nitride or from attaching to quartz media.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To culture pullulan, fermentors are often run for long periods of time to maximize pullulan production, on the order of several days. 9 For the hour 3 cells in our study, we have very little exopolymer, and due to the size (39.5 nm) and chemical information, it is apparently entirely uronic acid based. The size of this polymer is sufficient to cause steric repulsion between the fungal macromolecules and the AFM tip, but this repulsion does not prevent the cells from adhering strongly to silicon nitride or from attaching to quartz media.…”
Section: Discussionmentioning
confidence: 77%
“…A. pullulans strain NRRL Y-2331-1, which produces high yields of a nonpigmented form of pullulan, 9 was obtained from the United States Department of Agriculture (USDA). The growth media consisted of a complex nitrogen stock solution with sucrose as the carbon source, 5 containing (per 1 L of ultrapure water): 2.0 g of yeast extract, 0.5 g of (NH 4 ) 2 SO 4 , 1.0 g of NaCl, 0.2 g of MgSO 4 , 3.0 g of K 2 HPO 4 , 0.01 g of FeSO 4 , 0.01 g of MnSO 4 , 0.01 g of ZnSO 4 , and 50 g of sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…Different strains of A. pullulans produce substantially different titers and yields (on sugar substrates) of pullulan (Campbell et al, 2004;Gibson and Coughlin, 2002;West and Strohfus, 2001). Compared to the other strain, the NRRL Y-2311-1 produced a higher yield of unpigmented and reasonably higher molecular weight pullulan when cultivated under the conditions reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported optimum results when oil was added frequently during fermentation as a sole carbon source (Gibson and Coughlin, 2002;Jones and Porter, 1998;Ohta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation